Sanksi Pidana terhadap Pelaku Perburuan Gading Gajah di Indonesia - Made Dwi Mahayuni Dharmayanti; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2022)
Humans as social beings have different behaviors, traits and attitudes from one another. Humans do various ways to meet their needs, one of which is hunting. Hunting for elephant tusks is one of the causes of the decline in the elephant population. Thus, criminal sanctions against the perpetrators are one of the things that need to be considered to keep the elephant population from becoming extinct. This research aims to reveal the form of criminal sanctions against perpetrators of poaching elephant ivory in Indonesia. The method used is a normative legal research method with an approach to legal norms in accordance with the applicable laws and regulations. Sources of data used in the form of primary, secondary and tertiary data. Data were analyzed by descriptive method. The analyzed data reveals that the legal regulation regarding the prohibition of hunting for elephant ivory in Indonesia is contained in Article 21 paragraph (2) of Law Number 5 of 1990 and Article 17 jo. Article 20 of Government Regulation Number 13 of 1994. Criminal sanctions against perpetrators of poaching elephant ivory are regulated in Article 40 of Law Number 5 of 1990. Law enforcers are expected to provide the fairest sanctions and can provide a deterrent effect to perpetrators so that perpetrators and potential perpetrators do not do the same thing.